The Cycladic and Aegean Islands in prehistory - Berg, Ina (Routledge, 2018)
"Presents and analyses the development of the Cycladic and Aegean island communities from their earliest settlement in the Mesolithic through to the end of the Mycenaean period. By doing so, it traces the major environmental, cultural and religious transformations that these islands experienced. Fully up-to-date, this book incorporates into its narrative recent publications of old excavations as well as the results of important excavations undertaken over the last 20 years that have not yet been incorporated into the overall narrative of the Cyclades and Aegean's prehistory. The book's overall structure follows a straight-forward chronological sequence that delivers the necessary factual knowledge of sites, objects, debates and theoretical frameworks while the 'contextualisation' sections provide a critical analysis of the most important theme for the relevant time period"--